IMPLEMENTATION OF ENVIRONMNETAL MANAGEMENT ACCOUNTING (EMA) TO ACHIEVE COMPETITIVE ADVANTAGE - syarief gerald prasetya (The Accounting Journal of Binaniaga, 2021)
Environmental Management Accounting (EMA) is implemented to improve company's environmental performance. In the traditional accounting system, environmental management is always associated with costs that can reduce company profits. Unlike the case with EMA which makes environmental management an investment that is expected to increase profits while developing the company continuously to achieve competitive advantage. This study aims to analyze environmental management accounting in which can create a competitive advantage. The approach model used in this study is a theoretical approach. The results of the study explain that every company that carries out activities using environmentally friendly concepts through the implementation of Environmental Management Accounting (EMA) will have a higher value than other companies, because the implementation of Environmental Management Accounting (EMA) automatically companies have made good innovations on their products, production process and waste treatment. The conclusion of competitive advantage through the application of EMA can be viewed from the management strategy carried out by the company which includes a low cost strategy, differentiation strategy, focus strategy and innovation strategy